GE_GERICHTE P/6788/2011 vom 26. Juli 2011 - GE Cour de justice (2011)
; VOL(DROIT PÉNAL) ; PROCÉDURE PÉNALE ; ACCUSATION ; DROIT D'ÊTRE ENTENDU ; ACTE D'ACCUSATION | CP.139; CPP.9.1; Cst. 29.2; CPP.325.1